Out-of-hospital cardiac arrest during the COVID-19 pandemic in Paris, France: a population-based, observational study. (August 2020) - Marijon, Eloi; Karam, Nicole; Jost, Daniel; Perrot, David; Frattini, Benoit; Derkenne, Clément; Sharifzadehgan, Ardalan; Waldmann, Victor; Beganton, Frankie; Narayanan, Kumar; Lafont, Antoine; Bougouin, Wulfran; et al.
Summary: Background: Although mortality due to COVID-19 is, for the most part, robustly tracked, its indirect effect at the population level through lockdown, lifestyle changes, and reorganisation of health-care systems has not been evaluated. We aimed to assess the incidence and outcomes of out-of-hospital cardiac arrest (OHCA) in an urban region during the pandemic, compared with non-pandemic periods. Methods: We did a population-based, observational study using data for non-traumatic OHCA (N=30 768), systematically collected since May 15, 2011, in Paris and its suburbs, France, using the Paris Fire Brigade database, together with in-hospital data. We evaluated OHCA incidence and outcomes over a 6-week period during the pandemic in adult inhabitants of the study area. Findings: Comparing the 521 OHCAs of the pandemic period (March 16 to April 26, 2020) to the mean of the 3052 total of the same weeks in the non-pandemic period (weeks 12–17, 2012–19), the maximum weekly OHCA incidence increased from 13·42 (95% CI 12·77–14·07) to 26·64 (25·72–27·53) per million inhabitants (p<0·0001), before returning to normal in the final weeks of the pandemic period. Although patient demographics did not change substantially during the pandemic compared with the non-pandemic period (mean age 69·7 years [SD 17] vs 68·5 [18], 334 males [64·4%] vs 1826 [59·9%]), there was a higher rate of OHCA at home (460 [90·2%] vs 2336 [76·8%]; p<0·0001), less bystander cardiopulmonary resuscitation (239 [47·8%] vs 1165 [63·9%]; p<0·0001) and shockable rhythm (46 [9·2%] vs 472 [19·1%]; p<0·0001), and longer delays to intervention (median 10·4 min [IQR 8·4–13·8] vs 9·4 min [7·9–12·6]; p<0·0001). The proportion of patients who had an OHCA and were admitted alive decreased from 22·8% to 12·8% (p<0·0001) in the pandemic period. After adjustment for potential confounders, the pandemic period remained significantly associated with lower survival rate at hospital admission (odds ratio 0·36, 95% CI 0·24–0·52; p<0·0001). COVID-19 infection, confirmed or suspected, accounted for approximately a third of the increase in OHCA incidence during the pandemic. Interpretation: A transient two-times increase in OHCA incidence, coupled with a reduction in survival, was observed during the specified time period of the pandemic when compared with the equivalent time period in previous years with no pandemic. Although this result might be partly related to COVID-19 infections, indirect effects associated with lockdown and adjustment of health-care services to the pandemic are probable. Therefore, these factors should be taken into account when considering mortality data and public health strategies. Funding: The French National Institute of Health and Medical Research (INSERM)